Seroprevalence of HBV and HCV markers among young adult males in the Air Force in Florianópolis, South Brazil - Ana Maria Passos; Miguel Strazer Neto; Aricio Treitinger; Celso Spada (Universidade de São Paulo, 2012)
We investigated the prevalence of hepatitis B virus (HBV) and hepatitis C virus (HCV) serological markers of infection in young adults from the metropolitan region of Florianópolis who were conscripts of the Air Base of Florianópolis in the state of Santa Catarina, Brazil. A population-based cross-sectional seroprevalence study was conducted with 371 young males during a one year period starting in June 2009. Demographic characteristics, socio-economic characteristics and possible risk factors to HBV and HCV were assessed. Blood samples were analyzed for HBsAg, anti-HBc, anti-HCV and anti-HBs through automated microparticle enzymatic immunoassays (Abbott®, AxSYM System, Wiesbaden, Germany). None of the participants showed positivity to HBsAg or anti-HCV. The prevalence of anti-HBc was 1.6% (95% CI 0.6 - 3.5), and the prevalence of anti-HBs was 40.7% (95% CI 35.7 - 45.9). Unsafe sex was associated with positive anti-HBc in a bivariate analysis. There was a very low prevalence of past HBV infection and no cases of past HCV infection in a young adult population in the metropolitan region of Florianópolis. The very low prevalence of markers of infection and risk factors indicates a very optimistic future with respect to HBV and HCV infection in this population. Este estudo teve como objetivo investigar a prevalência dos marcadores sorológicos de infecção pelo HBV e HCV em adultos jovens na Região Metropolitana de Florianópolis, conscritos da Base Aérea de Florianópolis, Santa Catarina, Brasil. Trata-se de um estudo soroepidemiológico transversal de base populacional com 371 adultos jovens, no período de um ano a partir de junho de 2009. Foram pesquisadas características sócio-econômicas e possíveis fatores de risco para HBV e HCV. As amostras de sangue foram analisadas quanto à presença de HBsAg, anti-HBc, anti-HCV e anti-HBs pelo método imunoensaio enzimático automatizado de micropartículas (Abbott®, Sistema AxSYM, Wiesbaden, Alemanha). Nenhum dos participantes demonstrou positividade para HBsAg ou anti-HCV. A prevalência do anti-HBc foi de 1,6% (IC 95% 0,6 - 3,5) e do anti-HBs foi 40,7% (IC 95% 35,7 - 45,9). Relação sexual desprotegida associou-se com a positividade do anti-HBc na análise bivariada. Demonstrou-se prevalência muito baixa de infecção passada pelo HBV e ausência de HCV nesta população de adultos jovens na Região Metropolitana de Florianópolis. A particularidade desta prevalência muito baixa de marcadores de infecção e fatores de risco aponta para um quadro otimista em relação ao HBV e HCV no futuro para esta população.